Assessment Of Diluted Methanol As A Foaming Agent In Latex Modified Asphalt Mixture - Aziz, Muhammad Khuzaimi (Universiti Sains Malaysia, 2019)
Incorporation of latex in asphalt mixture has gain interest from the industry players as it makes road pavement more resilient. The elastomeric properties of latex make the binder stiffer and require more energy during asphalt mixture production. This would cause higher emission of greenhouse gases which harmful to the human health and the environment. This study aims to assess the applicability of diluted methanol as foaming agent in asphalt mixture incorporating latex produced at lower temperature. In this study, two designated amount of diluted methanol (1% and 3%) injected with 6% latex into the bitumen pre-heated at 135℃. While, the control and latex modified asphalt mixtures were prepared at 160℃. The asphalt mixture was prepared and compacted at 4% and 7% air voids depending on the designated test. Laboratory tests were conducted to identify the binder properties, service characteristics and mixture performance. The rotational viscosity, expansion rate and torsional recovery test were used to determine the viscosity of binder at different temperatures, foamability and its recovery after applying a torsional load, respectively. The service characteristics were evaluated through workability index, compaction energy index and coatability index that indicate the ease of mixing process, aggregates coating and compactibility of mixture. Moreover, the mixture performance tests were evaluated to identify the tolerance of mixture towards moisture damage, permanent deformation and shear force. Based on the result, the foamed binder exhibited lower viscosity compared to control asphalt and incorporation of latex has significantly improved the performance of binder. Better foaming index can be achieved by using higher amount of diluted methanol. The serviceability and mixture performance of foamed asphalt mixtures are comparable if not better than those asphalt mixtures prepared at higher temperature.